Covid-19 and Coal Industry in Indonesia: A Preliminary Analysis - Shofa Rijalul Haq; Ratna Mustika Dewi; Lidana Erfiandri; Puji Handayani Kasih; Aldin Ardian (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
Corona Virus Disease (COVID-19) pandemic dramatically impacted the energy sector. About 4.5% of global primary energy consumption dropped in 2020, where coal demand decreased by 220 million tons of coal equivalent. The drop was driven by lower electricity demand due to policies against Covid-19 (i.e., travel restriction, lockdown, and new standard). In particular, the COVID-19 crisis has already created profound uncertainties for the Indonesian coal mining industry as one of the world's largest coal producers and exporters. Coal is the primary energy source for Indonesian electricity, contributing to the national revenues. A debate about action to take, whether to focus on dealing with Covid-19 health or maintaining economic growth, is unavoidable. With the number of cases continuing to rise, we set out to investigate the impact of COVID-19 on Indonesia's coal mining industry. Rapid desk assessment and descriptive statistical approach were used in this study by evaluating secondary data during the pandemic, comparing with previous years before the COVID-19 pandemic. The results revealed a tangible transformation in coal demand, production, and price. Despite domestic coal consumption for power generation decreased, the coal price increased in mid of 2021 due to rising coal demand in China.